2020
DOI: 10.1021/acs.nanolett.0c02708
|View full text |Cite
|
Sign up to set email alerts
|

Real-Space Observation of Topological Defects in Extended Skyrmion-Strings

Abstract: Exotic topological spin textures such as emergent magnetic monopole/anti-monopoles (hedgehog/anti-hedgehog) in the metastable extended skyrmion-strings attract much attention to the fundamental physics owing to their novel electromagnetic properties. However, the direct imaging of such spin textures is lacking. Here, we report the real-space observation of emergent magnetic monopoles involved in extended skyrmion-strings by Lorentz transmission electron microscopy (TEM) in combination with micromagnetic simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 34 publications
1
46
0
Order By: Relevance
“…Previous Lorentz TEM observations have shown that in‐plane bias fields align the q ‐vector of Néel‐type helices perpendicular to the field direction in multilayered thin films, [ 18 ] while changing that of the Bloch‐type helices parallel to the field direction in the chiral magnet FeGe. [ 19–21 ] The results suggest that the external in‐plane field can induce a 90°‐rotation difference of q vectors for Néel and Bloch‐type twists in DMI‐stabilized systems. In addition, in‐plane fields align skyrmion strings along the field direction in a thick FeGe thin plate relative to its periodicity.…”
Section: Introductionmentioning
confidence: 97%
“…Previous Lorentz TEM observations have shown that in‐plane bias fields align the q ‐vector of Néel‐type helices perpendicular to the field direction in multilayered thin films, [ 18 ] while changing that of the Bloch‐type helices parallel to the field direction in the chiral magnet FeGe. [ 19–21 ] The results suggest that the external in‐plane field can induce a 90°‐rotation difference of q vectors for Néel and Bloch‐type twists in DMI‐stabilized systems. In addition, in‐plane fields align skyrmion strings along the field direction in a thick FeGe thin plate relative to its periodicity.…”
Section: Introductionmentioning
confidence: 97%
“…[ 8,11,15 ] The actualization of these unique topological features in real materials has pushed the investigation towards the less explored dimension along the length of SkS. [ 8–12 ]…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Although magnetic skyrmions are commonly illustrated as two-dimensional spin textures, [5][6][7] they naturally possess a 3D structure resembling elongated strings extending throughout the thickness of the sample up to several millimeters in length which align along the direction of the applied magnetic field. [8][9][10][11][12] These 3D spin textures known as magnetic skyrmion strings (SkS) are analogous to the vortex lines in superfluids [13] and type II superconductors, [14] manifest currentinduced non-linear dynamics and characteristics of magnonic nano-waveguides. [9,10] The broken inversion symmetry in the crystal lattice induces a Dzyaloshinskii-Moriya interaction (DMI) energy term that stabilizes SkS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These skyrmions are topologically nontrivial textures of the magnetization unit vector field m ( r ), whose filamentary structures resemble vortex-like strings or tubes, with typical diameters of tens of nanometers. The length of such a string is assumed to be limited only by the shape and size of the sample 19 , with direct observations confirming the formation of micrometer-long skyrmion strings 20 , 21 . Previous studies have suggested that magnetic skyrmion strings are (nearly) straight 19 – 25 .…”
Section: Introductionmentioning
confidence: 99%